ACCOUNTABILITY AND TRANSPARENCY OF VILLAGE ECONOMIC DEVELOPMENT - Moh Mustofa (Jurnal Scientia, 2023)
The importance of accountability and transparency in the implementation of village economic development is an element that must be met. The purpose of this study was conducted to determine the implementation of accountability and transparency in village economic development. This research method was conducted using a qualitative descriptive analysis. The results of this study concluded that the concepts of accountability and transparency in the implementation of village economic development in Gayam Village, Gayam District, Bojonegoro Regency can already be applied properly. Implementation of village economic development is carried out through agriculture, village markets and ponds. The results of this study can contribute theoretically that the implementation of village economic development can be carried out through agriculture, village markets and village ponds which are carried out with due regard to aspects of accountability and transparency.